COMPUTER GENERATION OF INVERSE GAUSSIAN SAMPLES BY ENVELOPE REJECTION - Lee, Wen Jau; Ong, S.H. (Malaysian Journal of Science, 2011)
The paper proposes a method for computer sampling from the inverse Gaussian distribution with parameters ,m by envelope rejection with the log-logistic distribution as the envelope distribution for m . The proposed rejection algorithm is shown to have good efficiency. (Keywords: inverse Gaussian, log-logistic distribution, computer sampling)